Las tareas matemáticas en la educación infantil un acercamiento a la utilización de herramientas tecnológicas en la enseñanza de las matemáticas Mathematical tasks in early childhood education: an approach to the use of technological tools in the teaching of mathematics - González Valencia, Heriberto (Universidad Santiago de Cali, 2020)
This research describes and characterizes the implementation of mathematical tasks in early childhood education in Colombia from the technological tools implemented in the teaching of mathematics. This study was carried out at the Santiago de Cali University - Colombia, and included the participation of 18 students from the 6th semester of the Preschool Degree Program, from which a sample of 3 girls and 4 boys from early childhood education was drawn. The implemented methodology was qualitative and descriptive, using sources of data collection of the mathematical tasks from the participant observation, photos, videos and field diaries typical of the students of Degree in Preschool. The results showed that children in early childhood education through the implementation of mathematical tasks, strengthened mathematical concepts established in the curricular standards and curricular guidelines implemented by the Ministry of National Education MEN, enriching the pedagogical practice of future preschool teachers.